أهمية الاتصال والثقافة التنظيمية في تحقيق أهداف المؤسسة الدينية - خضير رشيد (University of Eloued جامعة الوادي, 2023)
يتناول البحث أهمية الاتصال والثقافة التنظيمية في المؤسسة الدينية، على اعتبار أن هذا المفهوم أصبح يحتل مكانة بارزة في التسيير وتحقيق الأهداف المسطرة من قبل القائمين على المؤسسات المجتمعية، وتعتبر المؤسسة الدينية من أهم هذه المؤسسات وتحمل على عاتقها مسؤوليات هامة إزاء المجتمع، ويمثل نجاحها في تحقيق أهدافها مؤشرا على رقي المجتمع وتطوره. The research deals with the importance of communication and organizational culture in the religious establishment. This concept has come to occupy a prominent position in the management and achievement of the objectives established by those in charge of community institutions, and the religious establishment is considered one of the most important of these institutions that have important responsibilities towards society, and its success in achieving its objectives is an indication of the advancement and development of society.
Importance Of The Communication And Organizational Culture To Realize The Objectives Of The Religious Establishment
Keywords: الاتصال؛ الثقافة التنظيمية؛ المؤسسة الدينية; Communication; Organizational Culture; Religious Establishment